The Influence of Teacher Personality on Students English Learning Competencies - Cahya, Uci Dwi; Astari, Weni; Apriani, Wiwin; Zulida, Evi (Humanitatis : Journal of Language and Literature, 2024)
English teacher’s personality competency in improving students’ English language skills at Unggul Cut Nyak Dhien High School, Langsa City, is quite good. However, although the teacher’s personality is good, namely attitude and learning methods, it still needs to be improved in terms of using innovative learning media according to current developments because the teacher’s attitude and personality greatly influence students’ interest in learning. The method used in this research is descriptive qualitative. Data collection techniques use observation, interviews, and documentation, while data analysis uses Miles and Huberman’s theory through data reduction, data presentation, and data conclusions. The research results found that the personality competence of English teachers is very good, thereby increasing students’ competence in English; this can be seen through teacher discipline, good communication with students, fellow teachers, and the surrounding environment, and carrying out their duties as teachers well. The hope is that the results of this research can be used as a reading reference or increase knowledge.